Collaborative Transformation of University Teachers and Students to Improve Teaching Quality in the Context of Knowledge Fragmentation - Jiang, Danping; Yue, Jianzhi; Zhang, Tian; Zhang, Zhiping; Lu, Chaoyang (Journal of Research in Vocational Education, 2025)
In the digital era, information dissemination is characterized by fragmentation, which makes it difficult for learners to concentrate, and the knowledge they learn lacks systematicity and coherence, greatly affecting the quality of teaching in colleges and universities. In view of this phenomenon, this paper puts forward the changes that should be made in teaching and learning in response to the characteristics of knowledge fragmentation from the perspectives of both college teachers and students: 1. College teachers should accelerate the updating of the knowledge content of teaching, strengthen the systematicity and consistency of the curriculum, adopt more interactive teaching methods, guide students to learn and think in depth, and cultivate their independent learning ability. 2. Students should clarify their learning goals, make a learning plan, choose integrated learning resources, and form their own knowledge framework system by reviewing and summarizing for in-depth thinking. Thus, through the synergistic transformation of both teaching and learning, the negative effects of knowledge fragmentation can be avoided and the quality of teaching can be improved.